Fashioning Inclusion, Designing Internationalism: Pierre Cardin at the Brooklyn Museum: An exhibition review and dialogue between Matthew Webb and Matthew Yokobosky. Issue 1 (4th July 2020) - Webb, Matthew; Yokobosky, Matthew
ABSTRACT: In VAR 's new hybrid review–dialogue format, I talk with one of New York's leading museum‐based fashion curators about his work on the Brooklyn Museum exhibition Pierre Cardin: Future Fashion (July 2019–January 2020). The exhibition celebrates Cardin's role in the mid‐twentieth‐century "democratization" and "pluralization" of the European fashion system by pioneering a prêt‐à‐porter [ready‐to‐wear] collection, and spotlights his development of various strategies for licensing his designs, name, and initials to global partners. It also reveals a lesser‐known side of Cardin, showing his extensive travel and cultural advocacy for garment‐industry practitioners in China and Japan. In the dialogue, Yokobosky reflects on first meeting Cardin in Paris, remarks on producing the exhibit, and relays his perspective on why Cardin's "inclusive futurist" design ontology might be important for us to consider at this present historical moment. The article points toward two potentially productive but understudied areas for future anthropological research: fashion museums and exhibitions as sites for the organization of knowledge about social history and public culture, and the culturally (re)productive work of fashion curators—one form of "designerly" agency nested within museum institutions.